Graphene oxide/multi-walled carbon nanotubes/gold nanoparticle hybridfunctionalized disposable screen-printed carbon electrode to determine Cd(II) and Pb(II) in soil - WANG, Hui; Yin, Yuan; Zhao, Guo; Bienvenido, Fernando; Flores-Parrad, Isabel M; Wang, Zhiqiang; Liu, Gang (International Journal of Agricultural and Biological Engineering, 2019)
Cadmium (Cd) and lead (Pb) in soil or water environment cause the ecological destruction and environmental deterioration when their contents exceed the natural background values. To trace the concentrations of Cd(II) and Pb(II), a sensitive and selective electrode was developed using disposable screen-printed carbon electrode (SPE) immobilized with a composite film of reduced graphene oxide/carboxylation multi-walled carbon nanotubes/gold nanoparticle hybrid (RGO-MWNT-AuNP) through π-π bind. This highly conductive nano-composite layer, “RGO-MWNT-AuNP,” was characterized by scanning electron microscopy, UV-visible spectrometer, cyclic voltammetry, and electrochemical impedance spectroscopy. Square wave stripping voltammetry was applied to RGO-MWNT-AuNP/SPE to electroplate bismuth film and monitor the Cd(II) and Pb(II) simultaneously. To obtain high current responses, the detecting parameters were optimized. Under optimized conditions, the current responses showed a linear relationship with the concentrations of Cd(II) and Pb(II) in the range from 1.0 to 80.0 μg/L with a lower detection limit of 0.7 µg/L and 0.3 µg/L (S/N = 3), respectively. Finally, the prepared electrode was further employed to detect Cd(II) and Pb(II) in soil samples with good results.Keywords: electrochemical electrode, heavy metal contamination, screen-printed carbon electrode, graphene, gold nanoparticle, lead, cadmium, multi-walled carbon nanotubeDOI: 10.25165/j.ijabe.20191203.4300Citation: Wang H, Yin Y, Zhao G, Bienvenido F, Flores-Parrad I M, Wang Z Q, et al. Graphene oxide/multi-walled carbon nanotubes/gold nanoparticle hybridfunctionalized disposable screen-printed carbon electrode to determine Cd(II) and Pb(II) in soil. Int J Agric & Biol Eng, 2019; 12(3): 194–200.